2019
DOI: 10.5585/podium.v8i2.10665
|View full text |Cite
|
Sign up to set email alerts
|

O Uso da Tecnologia no Recrutamento e Seleção de Pessoas: Um Estudo no Setor Hoteleiro

Abstract: Objetivo: O presente estudo analisa a forma como a tecnologia da informação e comunicação tem sido utilizada no recrutamento e seleção de pessoas no setor hoteleiro. Metodologia/Abordagem: Realizou-se um estudo exploratório-descritivo de cunho qualitativo, a partir da aplicação de entrevistas, junto a gestores responsáveis pelas atividades de recrutamento e seleção de pessoas nos hotéis de Natal, RN, Brasil. Originalidade/Relevância: O trabalho evidencia tecnologias atuais que são utilizadas na captação de tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
1
0
4
Order By: Relevance
“…Avelar et al (2021) identified four HR Techs (in 2019) with solutions for R&S, and found that the difficulties for using HR Techs' services referred to the adequacy of the solution to expectations, especially those regarding a more assertive recruitment, both for reducing expenses with turnover and dealing with the lack of test customization. Silva and Barreto (2019) address the presence of AI-based technologies during the R&S process through social networks, both those created for the corporate environment, such as LinkedIn, and those not oriented specifically to this purpose, like Facebook (used to assess a company's reputation and engage people with a brand), Twitter (used to advertise vacancies through hashtags aiming to reach specific groups), and WhatsApp (used to advertise vacancies and establish a network).…”
Section: The Brazilian Literaturementioning
confidence: 99%
“…Avelar et al (2021) identified four HR Techs (in 2019) with solutions for R&S, and found that the difficulties for using HR Techs' services referred to the adequacy of the solution to expectations, especially those regarding a more assertive recruitment, both for reducing expenses with turnover and dealing with the lack of test customization. Silva and Barreto (2019) address the presence of AI-based technologies during the R&S process through social networks, both those created for the corporate environment, such as LinkedIn, and those not oriented specifically to this purpose, like Facebook (used to assess a company's reputation and engage people with a brand), Twitter (used to advertise vacancies through hashtags aiming to reach specific groups), and WhatsApp (used to advertise vacancies and establish a network).…”
Section: The Brazilian Literaturementioning
confidence: 99%
“…Nesse sentido são utilizadas noções de como operar máquinas e equipamentos, leitura de material indicados como estudo prévio com informações que vão desde o maquinário até o plano de carreira de cada cargo, aplicação de testes de aprendizagem dentre outros que inclusive incluem a dramatização que é baseada no faz de conta, ideal para cargos que exigem contato com pessoas, sendo uma junção de técnicas que conduzem o trabalhador ao conhecimento essencial para laborar de forma eficaz (SILVA, 2019).…”
Section: Consultoria Interna Em Rh Treinamento E Desenvolvimento De P...unclassified
“…Para existir a seleção é necessário o recrutamento, e o resultado do recrutamento afeta diretamente o da seleção. Em primeiro lugar está o recrutamento, na comunicação, divulgação e captação de profissionais, e em sequência acontece a seleção, realizando a escolha dos candidatos com melhor perfil para a vaga em aberto (Oliveira, 2005;Limongi-França, 2007;Pontes, 2015;Silva & Barreto, 2019).…”
Section: Processo De Agregar Pessoasunclassified